Analysis of the Development of Karyasari Village, Rengasdengklok District in Realizing the Sustainable Development Goals of the Village - Mulyana, Tiara Mahardika Puteri; Sujaya, Fista Apriani; Puspitasari, Meliana (West Science Accounting and Finance, 2024)
One of the sustainable development functions that is a priority program for the alocation of Village Funds in 2021 is Village SDGs. This research aims to know how SDGs are implemented in the development of Karyasari village. The theory in this research is the theory of Fonseca and Carvalho, who argue that sustainability can only be achieved through fulfilling the three SDGs requirements, namely balanced development in the social, economic and environmental fields. A data triangulation approach was used in this qualitative research to obtain data by combining several existing sources and types of data. The research results show that Karyasari Village has implemented 16 of the 18 SDGs goals. Judging from the implementation of the SDGs, Karyasari village applies 5 economic dimensions, 5 social dimensions and 6 environmental dimensions. For several SDGs goals, Karyasari Village has reasons why SDGs No. 12 concerning environmentally conscious village consumption and production has not been implemented because Karyasari village does not have a final waste bin. The village remains consistent in implementing the SDGs that have been achieved and the SDGs that have not been achieved, namely No. 12 concerning Environmentally Conscious Village Consumption and Production. It would be better for the village to be able to build a good waste management system if necessary and collaborate with partners.